2007
DOI: 10.1177/154405910708600510
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Corrosion and Cytotoxicity of Orthodontic Brackets

Abstract: The corrosion resistance of AISI 304 stainless steel (AISI 304 SS) and manganese stainless steel (low-nickel SS) brackets in artificial saliva was investigated. The cytotoxic effects of their corrosion products on L929 cell culture were compared by two assays, crystal violet, to evaluate cell viability, and MTT (3-[4,5-dimethylthiazol-2-yl]2,5-diphenyltetrazolium bromide), for cell metabolism and proliferation. The atomic absorption spectroscopic analysis of the corrosion products demonstrated that nickel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
(18 reference statements)
0
31
0
1
Order By: Relevance
“…16,29 It seems that corrosion extracts of stainless steel brackets do not alter viability in L929 cell culture but cause reduction of cellular metabolism. 30 This suggests that mitochondrial metabolism is the target of corrosion products. Nickel ions, when in the trivalent form, are exposed to mitochondrial redox metabolism, which leads to the formation of not fully reactive oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
“…16,29 It seems that corrosion extracts of stainless steel brackets do not alter viability in L929 cell culture but cause reduction of cellular metabolism. 30 This suggests that mitochondrial metabolism is the target of corrosion products. Nickel ions, when in the trivalent form, are exposed to mitochondrial redox metabolism, which leads to the formation of not fully reactive oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have evaluated the corrosion resistance of stainless steel in orthodontic wires and brackets [40][41][42][43] and have found that this alloy shows corrosion potential in different media, including the oral environment. House et al [44], in their review article, summarize corrosion types as follows:…”
Section: Corrosion and Elemental Releasementioning
confidence: 99%
“…The most frequent mechanisms of adverse reactions induced by metals are: a) corrosion, which is dependent on the presence of oxygen, chlorides, and non-noble metal alloys in the oral cavity, and b) the gradual and continuous release of ionic components from dental materials. Such ionic components are absorbed in the human body, either through the digestive system, oral mucosa, skin, or airways (Eliades and Athanasiou, 2002;Costa et al, 2007). The most common adverse reactions are caused by metal toxicity, sub-toxic reactions, hypersensitivity, and allergic contact dermatitis (Pedemonte et al, 2006).…”
Section: Introductionmentioning
confidence: 99%